Hubungan Demand Kelas Perawatan Berdasarkan Bed Occupancy Ratio Terhadap Pendapatan di Instalasi Pelayanan Rawat Inap - Addinda Intan Mayangsari; Budi Hidayat; Christina Nursarita Intama (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The condition of the COVID-19 pandemic experienced by Indonesia in early March 2019 had the effect of changes to policy rules in hospitals, demand for treatment classes in Inpatient Service Installations based on the Bed Occupancy Ratio (BOR) is an indicator of hospital performance that can be measured, apart from being an indicator BOR performance can also affect hospital revenues. This study aims to determine the relationship between demand for treatment classes based on BOR with income in Inpatient Service Installations in various hospitals. The research method was carried out using a literature review by analyzing various articles related to several keywords that the researchers analyzed, including : health demand, BOR, hospital income, and hospitals. A literature review was conducted through Google Scholar, Pubmed, and Garuda to conduct analysis according to articles relevant to the research title. The results of this study prove that with several methods of analyzing demand for treatment classes based on BOR, it clearly affects hospital income. This condition was clearly seen before the pandemic conditions, there was an increase in BOR followed by an increase in hospital income, but during the pandemic conditions, the BOR in inpatient rooms decreased, which affected the decrease in hospital income.